Is there a relationship between constipation and time of enuresis: single center study in Referral Hospital, Tehran - Imanzadeh, Farid; Sayyari, Ali-Akbar; Sharifian, Mostafa; Javaherizadeh, Hazhir; Tajik, Pantea (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction : Constipation is one of the multiple factors that cause enuresis. The correlation between enuresis and constipation is well established. But there is limited research on the correlation of time of voiding and constipation. Aim : To find a correlation between time of enuresis and constipation. Material and methods : This cross sectional study was carried out in Mofid Children’s Hospital, from January 2010 to June 2011. All patients with constipation or enuresis were included in this study and evaluated for both conditions. We classified cases according to time of enuresis in 3 categories. Data were analyzed by SPSS and Epi-info with χ 2 and t-test. Value of p below 0.05 was considered significant. Results : In this study, 560 patients who visited a physician with constipation (n = 400) or enuresis (n = 160) were included. We investigated children with constipation for enuresis, and children with enuresis for constipation. Finally, constipation was present in 480 cases and enuresis in 289 cases. Duration of constipation was 9.60 ±7.1 (1-42) weeks and duration of enuresis was 6.17 ±4.74 (1-25) weeks. Of 160 patients with enuresis, 80 (50%) had constipation. Of 400 patients with constipation, 129 had enuresis (32.25%). There was a significant correlation between duration of constipation and duration of enuresis (p < 0.001, Pearson test). Of 318 constipated boys, 148 (61.46) had enuresis. Of 162 girls with constipation, 61 (37.65%) had enuresis. The rate of enuresis among constipated boys was significantly higher than girls (p = 0.0001, χ 2 ). Of 560 patients, constipation and enuresis; only constipation; and only enuresis were found in 209 (37.32%), 271 (48.40%), and 80 (14.28%) cases respectively. Conclusions : Duration of constipation was correlated with duration of enuresis. The rate of enuresis in constipated boys was significantly higher than in constipated females. We strongly recommend careful inspection of both conditions in each patient who presents with one of them.